Impact of diabetes mellitus and chronic liver disease on the incidence of dementia and all-cause mortality among patients with dementia. Issue 47 (November 2017) - Kim, Hyun Min; Lee, Yong-ho; Han, Kyungdo; Lee, Byung-Wan; Kang, Eun Seok; Kim, Jaetaek; Cha, Bong-Soo
Abstract : Abstract: This study investigated the effects of the presence of type 2 diabetes mellitus (T2D) and/or chronic liver disease (CLD) on the incidence and prognosis of dementia during a 10-year period in Korea using a nationwide population-based dataset from the Korea National Health Insurance Service. To assess the impact of T2D and CLD on the incidence of dementia, we included subjects aged ≥60 years without dementia, T2D, and CLD from 2003 to 2005. We created another cohort for evaluating the all-cause mortality in subjects with dementia between 2003 and 2005. The participants were categorized into 4 groups: control (neither CLD nor T2D), CLD-only, T2D-only, and T2D-and-CLD groups, and they were followed up until 2013. The incidence of dementia was higher in the T2D-only group than in the control and CLD-only groups (2.78 vs. 2.04 and 2.00 per 1000 person-years). After adjustment for age, gender, and comorbid conditions, both T2D and CLD increased the risk of any type of dementia; however, the impact of CLD alone was much lower [hazard ratio (HR) 1.07, 95% confidence interval (CI): 1.06–1.08] than that of T2D alone (HR 1.27, 95% CI: 1.27–1.28). The risk of dementia did not significantly change in patients with the co-occurrence of T2D and CLD compared to those with T2D alone. The all-cause mortality rate was the lowest in the control group (2.59 per 1000 person-years) and the highest in the T2D-and-CLD group (3.77 per 1000 person-years). Presence of T2D or CLD alone was associated with higher mortality (HR 1.46 and HR 1.21, respectively) compared with in the absence of both the diseases. Furthermore, the presence of both the diseases further significantly increased the mortality rate compared to the presence of each disease alone (HR 1.67, 95% CI: 1.65–1.69). In conclusion, this study found that the incidence of dementia was much higher in patients with T2D. CLD was associated with a modest increase in risk of dementia; however, there was no additive effect with T2D. In the population with dementia, however, the presence of CLD was associated with high mortality in patients with or without T2D.